Evaluation of the Sensory Quality of Beef Jerky Using Celery Leaf Extract as a Source of Natural Nitrite - Arizona, Rizki; Palulungan, John Arnold; Ollong, Abdul Rahman; Saragih, Evi Warintan (JAS, 2025)
Dendeng is processed through salting and drying to extend its shelf life and develop a distinctive flavor. Synthetic nitrite in its processing plays a vital role in maintaining the red color and texture, inhibiting the growth of pathogenic microbes. However, the health risks due to the formation of carcinogenic nitrosamine compounds from the reaction of nitrite with amines in meat drive the search for safer natural alternatives. Celery leaves (Apium graveolens) are a potential candidate due to their natural nitrate content (1,496 ppm) that can be converted into nitrite through the activity of the enzyme nitrate reductase. Celery leaves also contain antioxidants that support product quality during storage. This study aims to evaluate the effectiveness of celery leaves as a substitute for synthetic nitrites in beef jerky, particularly in terms of sensory acceptance. This study is expected to serve as a foundation for developing healthier, more natural processed meat products and reducing dependence on synthetic chemicals. This study uses non-parametric analysis, specifically the Kruskal-Wallis Hedonic test followed by the Mann-Whitney test in a spider web model with four treatments of celery leaves, including P0 (control/without celery leaves), P1 (16g celery leaves), P2 (32g celery leaves), and P3 (48g celery leaves). The analysis results show that using celery leaves as a natural curing agent significantly affects color, tenderness, and flavor. The addition of celery leaves up to 16 grams has the best effect.